2000
DOI: 10.2134/agronj2000.9261077x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Development of Alfalfa Cultivars Selected for Higher Quality

Abstract: Alfalfa (Medicago sativa L.) maturity at the time of harvest greatly influences forage quality. The objective of this research was to determine if observed quality differences between high quality and other alfalfa cultivars were due to differences in morphological development. Two high‐quality cultivars (‘WL 252HQ’, ‘WL 322HQ’) and two check cultivars (‘5262’, ‘5454’) with similar fall dormancy ratings were established on a Murrill silt loam (fine‐loamy, mixed, mesic Typic Hapludult) in the spring of 1996. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 16 publications
5
41
0
6
Order By: Relevance
“…However, Sheaffer et al (1998) indicated on the basis of their experiment that ranking of alfalfa entries for forage quality was more affected by season than by either location or maturity of the alfalfa. Also Hall et al (2000) found no connection between growth period or sampling time and forage quality at alfalfa cultivars. The findings of their research indicated that the difference in quality between the high quality and traditional alfalfa cultivars was not due to differences in morphological development.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, Sheaffer et al (1998) indicated on the basis of their experiment that ranking of alfalfa entries for forage quality was more affected by season than by either location or maturity of the alfalfa. Also Hall et al (2000) found no connection between growth period or sampling time and forage quality at alfalfa cultivars. The findings of their research indicated that the difference in quality between the high quality and traditional alfalfa cultivars was not due to differences in morphological development.…”
Section: Resultsmentioning
confidence: 85%
“…Hall et al (2000) reported that the non-significant interaction between the alfalfa cultivars and growth periods indicates that the higher forage quality of high-quality cultivars is a stable phenotypic trait throughout the growing season.…”
Section: Resultsmentioning
confidence: 99%
“…The information summarized in Table 1 suggests that no overall variation for forage digestibility and contents of protein and neutral detergent fiber (NDF, associated with rate of forage ingestion by animals) has arisen from alfalfa breeding. However, successful selection for all of these traits has been performed and made available by specific "high-quality" alfalfa cultivars (Hall et al, 2000).…”
Section: Achieved Breeding Gainsmentioning
confidence: 99%
“…On the other hand, narrow-sense heritability values for these traits are reportedly modest, ranging from 0.18 to 0.39 (Guines et al, 2002). Selection for improved quality has produced varieties with consistently greater digestibility and protein content and lower NDF (Hall et al, 2000). The development of increasingly reliable near-infrared reflectance spectroscopy (NIRS)-based estimation has made possible and cost-effective the evaluation of many plants or families in breeding programs.…”
Section: Downloaded By [West Virginia University] At 06:45 20 Novembementioning
confidence: 99%
“…In a 4-yr study, Hall et al (2000) found greater crude protein (CP) and in vitro true dry matter disappearance (IVTDMD) and less neutral detergent fi ber (NDF) and acid detergent fi ber (ADF) in the fourth production year compared with the second and third production years. Reduced productivity with stand age can alter forage quality.…”
mentioning
confidence: 99%